(untitled) (Eurasian Research Bulletin, 2023)
The article revelas the results of the analysis of total chlorophyll, chlorophyll "a", chlorophyll "b" and carotenoids quantity in the leaves of sweet potato grown in local condition. In accordance to dispersion analysis of obtained data, the quantity of total chlorophyll, chlorophyll "a" and chlorophyll "b" of GulDU 1 and GulDU 2 varieties was in various levels respectively to Hazina, Hazina 1, Hazina 2 varieties. It has been determined from the results that the quantity of total chlorophyll, chlorophyll "a" and carotenoids in GulDU 2 variety was higher than in Hazina, Hazina 1, Hazina 2 and GulDU 1 varieties. It has been concluded that GulDU 2 variety is an effective for local condition and recommended to use it as valuable initial material in selection and breeding.